ZAKα/P38 kinase signaling pathway regulates hematopoiesis by activating the NLRP1 inflammasome - Rodríguez‐ruiz, Lola; Lozano‐gil, Juan M; Naranjo‐sánchez, Elena; Martínez‐balsalobre, Elena; Martínez‐lópez, Alicia; Lachaud, Christophe; Blanquer, Miguel; Phung, Toan K; García‐moreno, Diana; Cayuela, María L; Tyrkalska, Sylwia D; Pérez‐oliva, Ana B; et al. (EMBO molecular medicine, 2023)
Chronic inflammatory diseases are associated with hematopoietic lineage bias, including neutrophilia and anemia. We have recently identified that the canonical inflammasome mediates the cleavage of the master erythroid transcription factor GATA1 in hematopoietic stem and progenitor cells (HSPCs). We report here that genetic inhibition of Nlrp1 resulted in reduced number of neutrophils and increased erythrocyte counts in zebrafish larvae. We also found that the NLRP1 inflammasome in human cells was inhibited by LRRFIP1 and FLII, independently of DPP9, and both inhibitors regulated hematopoiesis. Mechanistically, erythroid differentiation resulted in ribosomal stress-induced activation of the ZAKa/P38 kinase axis which, in turn, phosphorylated and promoted the assembly of NLRP1 in both zebrafish and human. Finally, inhibition of Zaka with the FDA/EMA-approved drug Nilotinib alleviated neutrophilia in a zebrafish model of neutrophilic inflammation and promoted erythroid differentiation and GATA1 accumulation in K562 cells. In conclusion, our results reveal that the NLRP1 inflammasome regulates hematopoiesis and pave the way to develop novel therapeutic strategies for the treatment of hematopoietic alterations associated with chronic inflammatory and rare diseases.